2008
DOI: 10.4321/s1130-01082008000900010
|View full text |Cite
|
Sign up to set email alerts
|

Esofagitis necrosante aguda: análisis retrospectivo

Abstract: INTRODUCCIÓNLa esofagitis necrosante aguda (ENA) es una entidad de descripción muy infrecuente. Se reconoce por el aspecto negro difuso del esófago a la endoscopia, en asociación a cambios histopatológicos de necrosis de la mucosa. La necrosis es mayor en el tercio distal con terminación abrupta en la línea Z.La primera descripción endoscópica fue informada por Goldenberg y cols. (1) en 1990. La causa de la lesión no está completamente aclarada, aunque en ella parece intervenir un componente isquémico (1); obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
1
6
0
3
Order By: Relevance
“…The etiology of ANE remains unknown, some authors believe that ischemia is the main cause [2-4, 13], but massive gastroesophagic reflux [14] and NSAID intake could also be involved [7], It seems possible that all of these factor had contributed to development of ANE in this patient, this supports the idea that etiology could be multifactorial [15]. …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The etiology of ANE remains unknown, some authors believe that ischemia is the main cause [2-4, 13], but massive gastroesophagic reflux [14] and NSAID intake could also be involved [7], It seems possible that all of these factor had contributed to development of ANE in this patient, this supports the idea that etiology could be multifactorial [15]. …”
Section: Discussionsupporting
confidence: 64%
“…The black esophagus is a rare entity, which incidence has not been defined [3, 4], some studies show that it may be between 0.01% [5, 6] and 0.28 % [4]. A study performed among Japanese patients with UGB found an incidence of 6% [7].…”
Section: Discussionmentioning
confidence: 99%
“…This patient was affected by chronic ischaemic heart disease, hypertension and pneumonia and was subsequently diagnosed with ZES. AON reoccurrence is a rare event that has rarely been observed [11,12]. To our knowledge, only two other cases with AON relapse have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two other cases with AON relapse have been reported. Tanaka et al reported the case of a male patient with multiple comorbidities (diabetes mellitus, hypertension, hyperlipidaemia, and angina pectoris) with a reoccurrence after approximately 5 months from the first episode [11], and Ramos et al described a patient who developed a new AON after 4 months [12]. Even if recurrence is rare, it represents an important event to consider in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…It tends to be more frequent in critically ill patients, particularly those with refractory shock or systemic inflammatory disease. The estimated incidence ranges between 0.001% and 0.028% based on autopsy and endoscopic series 4 - 8…”
mentioning
confidence: 99%